2019
DOI: 10.1002/ijgo.12896
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a subcutaneous contraceptive implant training simulator

Abstract: Objective To design and fabricate a subcutaneous contraceptive implant insertion simulator, and to characterize the performance of nursing students trained with and without the simulator. Method A cross‐sectional study was conducted on nursing students in Ghana who had no previous training in the insertion of contraceptive implants. They were given standardized training in insertion of implants from 25 April to 26 April, 2016, and then were randomly assigned to an intervention or control group. The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Dery et al . (2019) and O'Flaherty and Costabile (2020) discovered that using simulations to insert subcutaneous contraceptive implants improved students' self-confidence and reduced their anxiety in a separate study conducted in Ghana among nursing students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dery et al . (2019) and O'Flaherty and Costabile (2020) discovered that using simulations to insert subcutaneous contraceptive implants improved students' self-confidence and reduced their anxiety in a separate study conducted in Ghana among nursing students.…”
Section: Resultsmentioning
confidence: 99%
“…According to the findings of Dery et al (2019) and Mikrogianakis et al (2011), the use of telesimulation-assisted medical doctors in Botswana improves their skills in the insertion of mechanical intraosseous needles. Other studies have found that the use of simulation assists in knowledge acquisition (Angelina et al, 2021;Nelissen et al, 2015;O'Flaherty and Costabile, 2020;Tjofl at et al, 2017Tjofl at et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] In this context, it is important to improve the nurses' cognitive, affective, and psychomotor learning domains or dealing with pre-eclampsia during undergraduate education. [6][7][8] Clinical nursing education, which is the major part of nursing education, contributes to better prepare nursing students for their future professional roles. [9][10][11][12] Nonetheless, nursing students in the clinical setting face multiple challenges such as the fear of making mistakes and harming a patient, discomfort of being evaluated by clinical trainers, and difficulties in dealing with emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses have a critical role in the management of pre‐eclampsia, and it is essential that they have appropriate intervention skills 4–6 . In this context, it is important to improve the nurses’ cognitive, affective, and psychomotor learning domains or dealing with pre‐eclampsia during undergraduate education 6–8 . Clinical nursing education, which is the major part of nursing education, contributes to better prepare nursing students for their future professional roles 9–12 .…”
Section: Introductionmentioning
confidence: 99%